2022
DOI: 10.1038/s41392-022-01190-w
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways and therapeutic interventions in gastric cancer

Abstract: Gastric cancer (GC) ranks fifth in global cancer diagnosis and fourth in cancer-related death. Despite tremendous progress in diagnosis and therapeutic strategies and significant improvements in patient survival, the low malignancy stage is relatively asymptomatic and many GC cases are diagnosed at advanced stages, which leads to unsatisfactory prognosis and high recurrence rates. With the recent advances in genome analysis, biomarkers have been identified that have clinical importance for GC diagnosis, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 635 publications
2
60
0
Order By: Relevance
“…To date, surgical resection is considered the main curative treatment option and chemotherapy is the most common treatment for GC [ 2 ]. Standard of first-line therapy for GC typically consists of 5-FU and a platinum-based agent including SOX (S-1 + oxaliplatin), XELOX (oxaliolatin + capecitabine), FOLFOX (leucovorin + 5-FU + oxaliplatin) and FLOT (5-FU + leucovorin + oxaliplatin + docetaxel) [ 3 ]. To date, two targeted therapies have been permitted to use in the clinic: trastuzumab (targeting HER2) and ramucirumab (targeting VEGF) [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, surgical resection is considered the main curative treatment option and chemotherapy is the most common treatment for GC [ 2 ]. Standard of first-line therapy for GC typically consists of 5-FU and a platinum-based agent including SOX (S-1 + oxaliplatin), XELOX (oxaliolatin + capecitabine), FOLFOX (leucovorin + 5-FU + oxaliplatin) and FLOT (5-FU + leucovorin + oxaliplatin + docetaxel) [ 3 ]. To date, two targeted therapies have been permitted to use in the clinic: trastuzumab (targeting HER2) and ramucirumab (targeting VEGF) [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, downregulated HP‐hDEmiRs were found to target TGF‐beta signaling, mitosis, translation, and gene silencing. These biological processes are important in cancer progression, and downregulation of the regulatory HP‐hDEmiRs possibly favor the overexpression of these processes 57 . Clearly, this pathogen uses HP‐hDEmiRs as surrogates to alter the host gene expression that paves toward carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Zhao et al found that USP28 was highly expressed in GC and was conducive to proliferation and metastasis, mainly due to its ability to increase LSD1 levels [ 53 ]. The same group subsequently designed and synthesized new [ 1 , 2 , 3 ] triazolo [4,5-d] pyrimidine derivatives as potent USP28 inhibitors. Among them, compound 19 potently inhibited USP28 activity with an IC 50 of 1.10 ± 0.02 μM and induced its degradation at higher doses, thereby exhibiting cytotoxic effects against GC cells [ 110 ].…”
Section: Usps and Gcmentioning
confidence: 99%
“…Based on estimates from the GLOBOCAN database, more than 1 million new GC cases and an estimated 769,000 GC deaths occurred worldwide in 2020 [ 1 ]. As with other cancer types, GC development is a multistage process involving genetic and epigenetic alterations [ 2 , 3 ]. In addition to host factors, other etiological factors, including a high-salt diet, tobacco use, and infectious agents, such as Helicobacter pylori ( H. pylori ) and Epstein–Barr virus (EBV), also play a significant role in the initiation and progression of GC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation